Viability Test of Hydrocarbonoclastic Bacteria Consortium Entrapted on Sawdust Material - Devia Hartono Puteri; Aditya Hikmat Nugraha; Yeti Darmayati; Agung Dhamar Syakti (Journal Omni-Akuatika, 2021)
Oil spills in the sea are generally prevented in various ways, one of them is the bioaugmentation method through bacterial entrapment on sawdust carriers. The entrapment of bacteria is one of the bacterial immobilization techniques. The potential of bacterial consortium on sawdust is still not widely used, especially in long-term storage. The purpose of this study was to obtain the viability of hydrocarbonoclastic bacterial consortium on sawdust after 0, 7, and 41 days of storage. The bacterial consortium consists of Bacillus aquimaris, B. megaterium, B. pumilus, Halobacillus trueperi, and Rhodobacteraceae bacterium. The samples were tested by culturing the immobilized bacterial consortium of 0, 7, and 41 days on falcon tubes containing crude oil and seawater. The viability of the immobilized bacterial consortium was tested for 28 days (days 0, 7, 14, 21, and 28) by enriched the bacterial populations periodically. The viability test was also supported by the measurement of environmental parameters on the 1st day and the 28th day such as DO, pH, salinity and, temperature. The results show that bacterial consortium in all storage periods was viable on sawdust carriers which related to the high number of bacterial populations on the 28th day. The most viable bacterial consortium on sawdust was the 0-day storage (9.59 x 108 CFU/ml) which was indicated by the increases phase at the end of the day. It was proved that the bacteria are still productive and could degrade petroleum hydrocarbons.